2018
DOI: 10.1111/nph.15277
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis downy mildew effector HaRxL106 suppresses plant immunity by binding to RADICAL‐INDUCED CELL DEATH1

Abstract: Summary The oomycete pathogen Hyaloperonospora arabidopsidis (Hpa) causes downy mildew disease on Arabidopsis. To colonize its host, Hpa translocates effector proteins that suppress plant immunity into infected host cells. Here, we investigate the relevance of the interaction between one of these effectors, HaRxL106, and Arabidopsis RADICAL‐INDUCED CELL DEATH1 (RCD1).We use pathogen infection assays as well as molecular and biochemical analyses to test the hypothesis that HaRxL106 manipulates RCD1 to attenuate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 90 publications
(139 reference statements)
3
66
0
1
Order By: Relevance
“…The other residues involved in NAD + binding are conserved in active PARPs, regardless of whether activity is mono-or poly-ADP ribosylation. By contrast, the human zinc finger antiviral protein (HsZAP, or PARP13) and Arabidopsis RCD1 lack two or more of the NAD + -binding residues and are catalytically inactive (Karlberg et al, 2015;Wirthmueller et al, 2018). In TASOR the key residues required for catalysis are even more degenerated than in ZAP or RCD1: all but one of them are replaced by hydrophobic amino acids ( Fig.…”
Section: Tasor Duf3715 Is a Parp Domainmentioning
confidence: 99%
“…The other residues involved in NAD + binding are conserved in active PARPs, regardless of whether activity is mono-or poly-ADP ribosylation. By contrast, the human zinc finger antiviral protein (HsZAP, or PARP13) and Arabidopsis RCD1 lack two or more of the NAD + -binding residues and are catalytically inactive (Karlberg et al, 2015;Wirthmueller et al, 2018). In TASOR the key residues required for catalysis are even more degenerated than in ZAP or RCD1: all but one of them are replaced by hydrophobic amino acids ( Fig.…”
Section: Tasor Duf3715 Is a Parp Domainmentioning
confidence: 99%
“…The interdomain regions of RCD1 are intrinsically disordered regions (IDRs), which likely provides flexibility in assuming the final overall protein conformation. RCD1 and its paralog, SRO1 (SIMILAR TO RCD ONE 1), can form homo-and heterodimers (Wirthmueller et al, 2018) and can be considered essential proteins since the rcd1 sro1 double mutant is not viable under standard growth conditions (Jaspers et al, 2009;Teotia & Lamb, 2011). In plants, the RST-domain is unique to the RCD1-SRO protein family and TAF4 proteins (Jaspers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, lots of progress has been made on researches of CK1s from plants, especially Arabidopsis. The four MUT9-LIKE KINASEs (MLK1-4) have revealed to collectively impact Arabidopsis growth and development by involving in multiple physiological processes [5][6][7][8][9]. Previously, we found that the mlk1 mlk2 double mutant with pleiotropic defects including dwarfism, altered leaf shape and low fertility, was hypersensitive to osmotic stresses [10], suggesting the essentiality for plant growth and stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MLKs, also described as Arabidopsis EL1-like (AEL) proteins, were documented to phosphorylate ABA signal receptors PYRABACTIN RESISTANCE/PYR-LIKE (PYR/PYL) proteins to promote their degradation by ubiquitination, and triple mutants of mlks were hypersensitive to ABA treatment due to eliminated ABA responses [8]. Interestingly, one of the triple mutants, mlk1,3,4, showed elevated level of salicylic acid (SA)-induced defense marker genes, and MLKs were identified as interacting proteins with RADICAL-INDUCED CELL DEATH1 (RCD1), a positive regulator of SA signaling [7]. Taken together, Arabidopsis MLKs collectively play critical roles in diverse biological processes including stress response, light signaling and immunity.…”
Section: Introductionmentioning
confidence: 99%